Experimental study on electrical power generation from a 1-kW engine using simulated biogas fuel - Hassan, S. (2019)
This chapter presents a simulated biogas with mixture of 60 methane (CH4) and 40 carbon dioxide (CO2) as a fuel for small 1 kW spark-ignition engine (SI). The simulated biogas fuel was tested on SI engine, and the engine performance was investigated at the constant engine speed under load transients. The SI engine was connected to load bank to generate a comparable result by using gasoline, liquefied petroleum gas (LPG), and natural gas as fuel in the engine to be evaluated with simulated biogas. The result showed that maximum specific fuel consumption forLPGand natural gaswas decreased by 10 and 23.4, respectively, when compared to gasoline, and it is proven that the simulated biogas has consumed more fuel (1254.83 kg/kWh) with only reach up to 780W. The power reduction of engine using simulated biogas was about 22 as compared to gasoline. In terms of engine efficiency, gasoline, LPG, and natural gas have generated 21, 20.7, 20.4, respectively, while simulated biogas generated only 0.16 of engine efficiency. Â© The Author(s), under exclusive licence to Springer Nature Singapore Pte Ltd. 2019.